Utilization of Heat Compressor in The Air Conditioning of The Ahu Direct Expantion System for Class 100,000 Cleanroom Rooms - Agung Laksono; Denny Prumanto; Amri Simbolon; Komarudin Komarudin (Greenation International Journal of Engineering Science, 2025)
Currently, the demand for cleanrooms is quite high. With the growth of the food industry, medical equipment, and hospitals, the need for these spaces has become increasingly important. Cleanroom classifications are regulated in various literature, such as ISO, SNI, NFPA, and others. In ISO 14644-1, cleanroom classification is divided into several categories: Class 100,000 (ISO 8), Class 10,000 (ISO 7), Class 1,000 (ISO 6), and Class 100 (ISO 5). The differences between these classifications lie in temperature, humidity, air changes per hour, particle quality, and airflow distribution.To maintain humidity, electric heaters are generally used as equipment. The energy requirement is quite high, and in an AHU system, this device creates an additional heat load because it generates the full sensible load. In this study, the use of a heat compressor or heat recovery unit could be an option for maintaining humidity in a room conditioned by an HVAC system. The flow rate of the high-temperature, high-pressure refrigerant will be regulated using a solenoid valve triggered by a humidity sensor. A defrost mechanism will be implemented within the heat recovery coil to prevent freezing within the system. The results of this study state that the energy required for a cleanroom AHU system that uses heat recovery for air humidity conditioning is more efficient than using an electric heater.